Variability in nutritional composition and phytochemical properties of red pitaya (Hylocereus polyrhizus) from Malaysia and Australia - Ramli, Nurul Shazini; Rahmat, Asmah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
The present work sought to investigate the nutritional composition and phytochemical properties of red pitaya (Hylocereus polyrhizus) juices from Malaysia and Australia and to determine the optimum ethanol concentration (in the range of 0-100% ethanol) for the extraction of phenolic, flavonoid and betacyanin contents. The predominant macronutrient in red pitaya juice was carbohydrate while potassium and vitamin A were the major mineral and vitamin content. Red pitaya juice from Malaysia achieved optimal total phenolic content at 20% of ethanol (20mL ethanol in 100mL water, v/v); total flavonoid content at 60% (v/v); and betacyanin content at 0% (v/v). Red pitaya juice from Australia achieved the maximum total phenolic content at 60% (v/v); total flavonoid content at 20% (v/v); and betacyanin content at 80% (v/v). Nutritional composition and the phytochemical properties of red pitaya in Malaysia and Australia were significantly different suggested the role of environmental factors like soil and climate on the phytochemical properties of red pitaya.